2019
DOI: 10.1039/c9qm00505f
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-narrow bandgap non-fullerene acceptors for organic solar cells with low energy loss

Abstract: Two ultra-narrow bandgap non-fullerene acceptors (NFAs), 4TO-T-4F and 4TO-Se-4F, were designed and synthesized for application in organic solar cells (OSCs). Thiophene and selenophene were used as p-spacers to extend the effective conjugated length via intramolecular noncovalent OÁ Á ÁS or OÁ Á ÁSe interactions and lower the bandgap. Both NFAs, 4TO-T-4F and 4TO-Se-4F, showed strong absorbance in the range of 700-1000 nm in the near-infrared region with an ultra-narrow bandgap of B1.30 and B1.27 eV, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…In this specific research field, low bandgap materials are actively researched as these compounds can also be easily oxidized and transfer an electron from the electrondonating material towards the electron-accepting one upon sunlight irradiation. [20][21][22][23] Low bandgap materials are also now extensively studied in photopolymerization due to the improved light penetration in the photocurable resins at long wavelength. [24][25][26][27][28] Thus, if the light penetration in the resin is limited to a few hundreds of micrometers at 400 nm, this latter can reach 5 cm at 800 nm, justifying the search for new structures.…”
Section: Introductionmentioning
confidence: 99%
“…In this specific research field, low bandgap materials are actively researched as these compounds can also be easily oxidized and transfer an electron from the electrondonating material towards the electron-accepting one upon sunlight irradiation. [20][21][22][23] Low bandgap materials are also now extensively studied in photopolymerization due to the improved light penetration in the photocurable resins at long wavelength. [24][25][26][27][28] Thus, if the light penetration in the resin is limited to a few hundreds of micrometers at 400 nm, this latter can reach 5 cm at 800 nm, justifying the search for new structures.…”
Section: Introductionmentioning
confidence: 99%
“…15 These high performance characteristics have been attributed in part to its long wavelength absorption onset (B900 nm) and complementary donor and acceptor absorption, large absorption extinction coefficients, and moderate HOMO and LUMO energy offsets. 5,[16][17][18][19] More in depth studies by Karki et al and Perfigon-Toro et al have identified several additional factors which may be critical to this blend's high performance, including efficient charge generation with barrierless CT state dissociation, and a nanomorphology favourable for charge separation. 15,20,21 The achievement of both high EQEs over 80% (up to 900 nm) and a low voltage loss in this blend has been highlighted as particularly remarkable.…”
mentioning
confidence: 99%
“…[59] These n-type polymers were prepared according to Stille cross-coupling polymerization of f-BTI2-DT, f-BTI2-HD, and FT monomers using various feed ratios between f-BTI2-DT and f-BTI2-HD having 2-DT and 2-HD side-chains, respectively (Scheme S1, Supporting Information). [59,60] The polymers are designated as PBTI2(xHD)-FT, where x (i.e., 30,50,70) represents the percentage of f-BTI2-HD relative to both f-BTI2 units (f-BTI2-HD þ f-BTI2-DT). The copolymer PBTI2(0HD)-FT was also synthesized for comparison.…”
Section: Syntheses and Properties Of Terpolymersmentioning
confidence: 99%
“…[22,23] BHJ film morphology with nanoscale phase separation and bicontinuous interpenetrating network is one of keys for achieving highly efficient OSCs. [24][25][26][27][28][29][30] Among various morphology tuning strategies, varying the donor:acceptor (D:A) ratio in BHJ active layer plays a primary and critical role. [31,32] For small molecule-based OSCs, the efficiency and stability are relatively sensitive to D:A ratio, signifying that a slight deviation from the optimal blend ratio can make a large negative impact on PCEs.…”
Section: Introductionmentioning
confidence: 99%